Multiple Brain Abscesses by an Air Gun Shot: A Case Report - Mohammad Jamali (Thieme Revinter Publicações Ltda., 2021)
Introduction Low-velocity penetrating brain injury is not prevalent. In some conditions such as childhood, and with the penetration of a pellet in weak spots of skull, low-velocity penetrating brain injury is expected; however, high-velocity projectiles have also been reported as the cause of severe brain injuries. One of the complications of penetrating brain injury is infection, in which different types of microorganisms play a role. The Streptococcus genus is the leading cause of abscess formation in non-traumatic patients. Multiple brain abscesses are not common. Case Presentation A 10-year-old boy with penetrating brain injury caused by an air gun pellet, who developed signs and symptoms of high intracranial pressure 18 days after the trauma. After the imaging scans and the detection of multiple brain abscesses and severe brain edema, prompt surgical intervention was performed for all three lesions in a single operation. The culture of a pus specimen was positive for Streptococcus species, and, with adequate antibiotic therapy, the patient was discharged from the hospital in good condition. Conclusion Brain injury with air gun shot is not prevalent. The penetration of a low-velocity air gun pellet in weak points of the skull (such as the orbit, the squamous portion of the temporal bone, and the cranial suture), specially in children, can cause significant brain injuries.